Temperature dependence of DNA translocations through solid-state nanopores. (12th June 2015) - Verschueren, Daniel V; Jonsson, Magnus P; Dekker, Cees
Abstract In order to gain a better physical understanding of DNA translocations through solid-state nanopores, we study the temperature dependence of λ-DNA translocations through 10 nm diameter silicon nitride nanopores, both experimentally and theoretically. The measured ionic conductance G, the DNA-induced ionic-conductance blockades <?CDATA Δ G?> <?MML Δ G ?><inline-graphic xlink:href="ark:/27927/pgj14jtmfqv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and the event frequency Γ all increase with increasing temperature while the DNA translocation time τ decreases. G and <?CDATA Δ G?> <?MML Δ G ?><inline-graphic xlink:href="ark:/27927/pgj14jtmdps" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> are accurately described when bulk and surface conductances of the nanopore are considered and access resistance is incorporated appropriately. Viscous drag on the untranslocated part of the DNA coil is found to dominate the temperature dependence of the translocation times and the event rate is well described by a balance between diffusion and electrophoretic motion. The good fit between modeled and measured properties of DNA translocations through solid-state nanopores in this first comprehensive temperature study, suggest that our model captures the relevant physics of the process.